FINANCING AND OVERSIGHT OF THE APPLICATION OF INVASIVE MEASURES FOR THE PURPOSE OF SECURITY AND DEFENSE (Annual of the Faculty of Philosophy in Skopje, 2023)
Invasive measures, as special investigative measures are defined, are ante delictum measures. They are applied only in situations in which the evidence cannot be obtained by conventional methods, and are needed for the smooth conduct of criminal proceedings. The financial means for the application of these invasive measures for the needs of defence and security are allocated with a budget by the legislative authority.The main hypothesis of this paper states that: supervision over the application and financing of the implementation of special investigative measures has a positive impact / or is in direct correlation with the effective construction/development and functioning of the security-defence system, especially from the aspect of the principles of: good governance, transparency, accountability, proportionality, and efficient application of financial resources.Starting from the indicated hypothesis, the research in the paper is based on two variables: independent variable, i.e., the supervision over the application and financing of the implementation of the special investigative measures, and a dependent variable, i.e., the effective development and proper and efficient functioning of the security-defence system.From a methodological point of view, the paper uses a combined approach of qualitative and quantitative analysis, through research, measurement, and comparison of: adopted international standards regarding the application of special investigative measures, the regulations in the Macedonian normative framework, the content of the instructions and the implementation manuals of the special investigative measures by the relevant institutions in the Macedonian society.
Keywords: invasive measures; special investigative measures; reforms; financing; security sector